BEYOND THE GREEN HORIZON: UNPACKING THE IMPACT OF REGENERATIVE HRM ON SUSTAINABLE EMPLOYABILITY IN THE DIGITAL TRANSFORMATION ERA - Priskilla E.E. Napitupulu; Janice Carysa Siahaya; Tania Monica Potu (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
Purpose, This research addresses the critical structural paradox of digital transformation within the contemporary labor market by investigating the impact of Regenerative Human Resource Management (HRM) on Sustainable Employability. Amidst the high-pressure digital pivoting of the financial sector in Surabaya, Indonesia, this study examines how restorative organizational practices influence long-term career vitality through the mediating role of Affective Commitment and the moderating influence of Digital Mindset. Design/methodology/approach, A quantitative-explanatory research design was employed, utilizing a self-administered survey to collect primary data from 128 permanent employees at Bank X Surabaya. The research framework was analyzed using PLS-SEM via SmartPLS 4.0. Findings, The empirical results reveal a significant paradoxical finding where Regenerative HRM does not directly impact Sustainable Employability. Instead, the relationship is characterized by full mediation through Affective Commitment. This indicates that restorative practices only enhance career longevity when they successfully foster deep emotional identification with the organization. Furthermore, Digital Mindset was found to be an insignificant moderator, suggesting that psychological and emotional bonds are more critical than cognitive-technological orientations in ensuring human capital sustainability amidst aggressive digitalization. Originality,This study contributes to the emerging discourse on regenerative economics by shifting the strategic focus from resource utilization to active human restoration. By identifying a full mediation mechanism, this research establishes a novel framework for sustainable human capital management in emerging economies, asserting that technological excellence must be achieved in tandem with the proactive replenishment of human energy and emotional trust.